Tomorrow Will Always Come, I am a Last-Minute Person: Validation of the Active Procrastination Scale-Bahasa Indonesia - Purwanto, Cynthia Vivian; Natalya, Lina (Makara Human Behavior Studies in Asia, 2019)
Procrastination, the habitual delaying of tasks, has long been considered to negatively affect procrastinators. Chu and Choi (2005), however, have newly recognized active procrastination, a form that has positive effects on procrastinators. This study aims to validate the use of the Active Procrastination Scale (APS) in bahasa Indonesia. In this validation, 239 undergraduate students completed online questionnaires consisting of the APS and other measurements (GPA, Pure Procrastination Scale (PPS), Academic Motivation Scale (AMS), and International Personality Item Pool (IPIP-50 item) in Indonesian. The data was analyzed using confirmatory factor analysis (CFA), exploratory factor analysis (EFA), reliability analysis, intra-correlation analysis, and correlation analysis with other criteria. Both CFA and EFA revealed that all items matched the same factors as Choi and Moran (2009)’s original design (RMSEA ≤ 0.08, GFI ≥ 0.9, CR ≥ 0.7, AVE ≥ 0.5). In addition, all dimensions were reliable (CITC ≥ 0.3, α ≥ 0.6). Meanwhile, intra-correlation analysis indicated that each dimension correlated with all others, in keeping with previous findings. The same findings were also found in correlation analysis. Each dimension showed the same correlation patterns with other criteria as the prior findings. In conclusion, the APS-Bahasa Indonesia is a valid procrastination measurement.